Data envelopment analysis with GAMS: A Handbook on productivity analysis and performance measurement - Emrouznejad, Ali; Petridis, Konstantinos; Charles, Vincent (Switzerland Springer, 2023)
This book provides a comprehensive and practical introduction to Data Envelopment Analysis (DEA). These models are presented in the context of the GAMS software, which is a powerful tool for mathematical programming models. This book serves two educational purposes: it introduces readers to DEA models and provides examples using GAMS.
Keywords: Data envelopment analysis Logiciels; Data envelopment analysis computer programs; Data envelopment analysis